The effect of a vibration absorber on the damping properties of alpine skis - Schwanitz, S.; Griessl, F.; Leilich, C.; Krebs, R.; Winkler, B.; Odenwald, S. (Proceedings, 2018)
Coupled bending-torsion vibrations at the shovel are a severe problem when running an alpine ski at high velocities on hard or icy slopes. Thus, a major goal for ski manufacturers is to dampen vibrations through a proper multi-material design and/or additional absorbers. The aim of this study was to examine the effectiveness of a particular vibration absorber on a commercial slalom ski through a series of laboratory tests as well as a subjective field evaluation. Therefore, two identical pairs of ski were used and the absorber was deactivated on one pair. Laboratory tests revealed reductions of 5% to 49% of bending vibrations on skis with activated absorber. Subjective evaluation by 6 subjects suggested minor differences in the mean of the evaluated criteria turnablity, edge grip, steering behavior and stability towards a better performance of the skis with activated absorber. Subjects were able to identify the absorber mode with a success rate of 61.1%.